Penerapan Metode Profile Matching untuk Penempatan Karyawan Berbasis Kompetensi di Bidang IT - Dedy Mulyadi; Teguh Maulana Hidayatulloh (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2022)
Placement of employees is one of the complex problems in the world of work. The discrepancy between work placement and the ability of employees who are placed in areas of work that are not in accordance with their expertise will certainly have an impact on work comfort which also affects work performance. For that we need a decision support system that is able to be a solution in dealing with problems faced by human resource managers in the difficulty of selecting candidates to occupy vacant positions. By applying the profile matching method in the employee job placement system, it can help the role of human resource managers in finding candidates who have a great chance to fill positions according to the required criteria. A feasibility test has been carried out on the developed system with a percentage value of 93.9%, which means the system is in the "Very Eligible" category for use.